Information-Limited Parallel Processing in Difficult Heterogeneous Covert Visual Search. - Dosher, Barbara Anne; Han, Songmei; Lu, Zhong-Lin (Journal of Experimental Psychology. Human Perception & Performance, 2010)
Difficult visual search is often attributed to time-limited serial attention operations, although neural computations in the early visual system are parallel. Using probabilistic search models (Dosher, Han, & Lu, 2004) and a full time-course analysis of the dynamics of covert visual search, we distinguish unlimited capacity parallel versus serial search mechanisms. Performance is measured for difficult and error-prone searches among heterogeneous background elements and for easy and accurate searches among homogeneous background elements. Contrary to the claims of time-limited serial attention, searches in heterogeneous backgrounds instead exhibited nearly identical search dynamics for display sizes up to 12 items. A review and new analyses indicate that most difficult as well as easy visual searches operate as an unlimited-capacity parallel analysis over the visual field within a single eye fixation, which suggests limitations in the availability of information, not temporal bottlenecks in analysis or comparison. Serial properties likely reflect overt attention expressed in eye movements. Reprinted by permission of the publisher.